(untitled) (Praxis Educativa, 2024)
Through the recognition of the qualities of plants that promote life, the study proposes these characteristics as necessary for the generation of living environments in education and research. Autopoietically, we identify relationships of sensitivity, collaboration, movement, travel, communication, memory and care. We value these qualities for the learning, change and transformation environments necessary in Education, which constitute dynamic, self-organized, changing and complex environments that are recognized as narrative environments. This work contributes to the understanding of life-research as an investigative and narrative experience, which from bioinspired research models, makes research possible as an experience of life itself that happens in its future.